Is there an easy way to solve a system like this one?
x y/(3x-4y)=2/11
y z/(2y+3z)=6/5
x z/(x-z)=3/2
Luke
Luke53 wrote:the first eqn is the same as:
(1/x)+(1/y)=3/8 (1)
the second eqn is:
(1/y)+(1/z)=5/8 (2)
the third eqn:
(1/x)+(1/z)=6/8 (3)
Luke53 wrote:Can one transform the three equations into the 1/x + 1/y form like in the previous example?
Luke53 wrote:I know that : x y /(x+y) = 8/3 is the same as 1/x + 1/y = 3/8
Could this sort of transformation also be done with: x y / (3x - 4y) = 2/11 ?